Ultrahigh temporal contrast performance of the PHELIX petawatt facility. (10th November 2016) - Bagnoud, V.; Wagner, F.
Abstract : We report on the temporal contrast performance of the PHELIX facility in view of the requirements imposed by solid-target interaction experiments. The requirement analysis for the nanosecond and picosecond temporal contrast is derived from empirical data and simple theoretical modeling, while the realization shows that using an ultrafast optical parametric amplifier and plasma mirrors enables meeting this specification.